INDUCTION OF CYCLICITY IN MURRAH BUFFALO-HEIFERS DURING SUMMER USING DIFFERENT HORMONAL PROTOCOLS - SINGH, VIRENDAR; MALIK, R K; SINGH, P; TULl, R K; VERMA, A K; CHANDOLIA, R K (The Indian Journal of Animal Reproduction, 2023)
Twenty four sexually mature, acyclic buffalo heifers were randomly and equally divided into four groups.Group A was kept as control in which no treatment was given. Group B received CIDR on day O (start of experiment),500 I.U. PMSG (day 9), removal of CIDR(day 10)and 1500 I.U. eCG at the time of insemination. GroupCanimalswere subjected to modified Ovsynch protocol where 500 I.U. PMSG wa,, administered (day 0) followed by 16 μgGnRH analogue (day 3), 500 μg cloprostenol(day 10)and second injection 16 μg GnRH (day 12). Group Danimalsreceived 500 mg hydroxyprogesterone and 10 mg estradjol valerate (day 0) followed by 500 μg cloprostenol_ and500 I.U. PMSG on day 7 and 9, respectively. Estrus was exhibited in 100% (Group B), 66. 7% (Group C and D) and33.3% (Group A). The duration of estrus was also higher in group B (28.2±6.12 hrs) as compared to group A(16.0±2.00 hrs) and group D (17.0±2.52 hrs). The pregnancy rate from insemination at induced estrus was 50.0,50.0, 16. 7and 50.0 per cent in group B, D, C and A, respectively. The results of the present in~estigation revealedthat differerit hormonal combinations were effective in inducing cyclicity and conception at first service as comparedto untreated animals. Therefore, it is concluded that use of progesterone based protocols during summer seasonis good for induction of estrus and improved conception rates in acyclic sexually mature buffalo heifers.
Keywords: Buffalo-heifers; Cyclicity; Fertility; Hormonal protocols; Summer